Malignant Transformation of Labial Lichen Planus: A Case Report and a Review of the Literature - Fouzia, HAKKOU; Yousra, ZEMMOURI; Saliha, CHBICHEB (International Journal of Innovative Research in Medical Science, 2021)
Oral Lichen Planus (OLP) is a chronic inflammatory dermatosis usually benign that can affect skin, integuments and mucosal membranes presented with various clinical appearances. Typically characterized by the presence of white lace-like lesions, with or without atrophic or erosive areas. Its diagnosis is based on the clinical examination and histological analysis. In most of the cases, the OLP has a benign evolution but malignant transformation may occur justifying the strict surveillance of the disease and effective treatment of relapses. We report the case of a 58-year-old man, without specific and non-smoking history, reported to the Oral Surgery Department of the Consultation Center of Dental Treatment of Rabat, presenting oral lesions lasting for three years. The intraoral examination and biopsy were concluded an erosive oral lichen planus. Two years after, the labial lesion changed its appearance. Pathological diagnosis confirmed the presence of squamous cell carcinoma. Total surgical excision was performed with respect of carcinologic resection margins. The present case supports the view that OLP may undergo malignant transformation, and that this does not require exogenous carcinogens. Oral lichen planus is a potentially malignant disorder with a capacity, although low, for malignant transformation. Of all the factors related to the process of malignant transformation, the chronic inflammation seems to be the key factor in the development of oral cancer. The highest rate of malignancy was noted in erythematous and erosive lesions. In this way, follow-up of OLP patients could be carried out more efficiently and appropriately.